Pengaruh Perceived Organizational Support dan Kepuasan Kompensasi terhadap Kinerja Karyawan dengan Employee Engangement Syariah sebagai Variabel Intervening (Studi pada Karyawan PT. Perkebunan Nusantara IX, Kebun Balong, Kab. Jepara, Jawa Tengah) - Ichsan Damar Rahardjo; Edy Raharja (ITB AAS INDONESIA Surakarta, 2023)
Indonesia has a plantation area of 25,302,200 hectares (BPS Data, 2021). One of the business entities that is a source of foreign exchange for the country is PT. Perkebunan Nusantara IX, a state-owned company and a subsidiary of PTPN III (Holding) which owns palm oil, sugar cane, rubber, coffee and tea commodities. PTPN IX has 15 gardens spread throughout Central Java province, one of which is Balong Gardens. Balong Gardens is one of the business units owned by PTPN IX located in the Kab. Jepara, Central Java whose main commodity is rubber plants which produce RSS (Ribbed Smoked Sheet) and Lump. Company goals can be achieved if human resource management is managed professionally so that the company can get employees who work optimally and make a positive contribution to the company. The aim of this research is to analyze the direct and indirect roles in improving employee performance The type used in this research is quantitative. This research has a population, namely workers at PT. Perkebunan Nusantara IX Kebun Balong, Jepara Regency, Central Java, as many as 539 people. Perceived organizational support has a positive and significant effect on employee performance at PT. Perkebunan Nusantara IX, Balong Gardens. The better the PT support. Perkebunan Nusantara IX, Kebun Balong to employees will further improve the quality of performance of all employees. Employee satisfaction also has a positive and significant effect on employee performance at PT. Perkebunan Nusantara IX, Balong Gardens. Compensation practices that have been implemented by PT. Perkebunan Nusantara IX, Kebun Balong is on the right track by carrying out digitalization in the process of distributing employee rights both financially and non-financially. The comfort felt by employees makes employees feel satisfied and tries to improve their performance for the company. The variables examined in this research include perceived organizational support and employee satisfaction. The most influential variable is employee satisfaction compared to perceived organizational support on employee performance at PT. Perkebunan Nusantara IX, Balong Gardens. PT. Perkebunan Nusantara IX, Kebun Balong needs to take strategic steps to increase employee engagement, especially when climate conditions do not allow employees to work. Maintain employee motivation and maintain employee physical fitness so that they are more connected to the company.